From sunlight to electricity - "Sinha, Shirish (ed.) ; Shukla , Anand (ed.) ; Hazarika ,Nand" (New Delhi, 1998)
From Sunlight to electricity : Solar Photovoltaic applications is a compilation of information that gives the readers an overall understanding of the photovoltaic (PV) sector in India, designs and applications of specific devices and related benefits, finance, and policies. The document also discusses the PV technology programme in India. the issues therein, and its future directions. The information has been presented in a format that it easy for the readers to understand and apply.The readers will find the information given in this document useful in assessing the potentialof such systems. It serves the interest of all the stakeholders in the PV sector, such as policy-makers, governemnt officials, non-governmental organizations, and academic and research organizations.
Keywords: Energy